TIBA PINAH, RITUAL TOLAK BALA ORANG BAJAU DI KABUPATEN TOJO UNA-UNA SULAWESI TENGAH - Purba, Jhon Rivel; Slippy, Janneke Peggy (Jurnal Tradisi Lisan Nusantara, 2023)
This study aims to find out how the process of carrying out Tiba Pinah, which is a ritual of rejecting reinforcements for the Bajau people in Tojo Una-Una Regency, Central Sulawesi. The research was conducted in two villages, namely Labuan Village, Ratolindo District and Kabalutan Village, Talatako District. This research uses qualitative methods by conducting interviews, observations and documentation. The results of the study show that the ritual performance of the Bajau people is an integral part of their belief in the ruler of the sea. The Tiba Pinah ritual that is still maintained and carried out by the Bajau people in Tojo Una-Una aims for treatment, search for missing persons, and ease of sustenance. Arriving Pinah is not only carried out at sea, but also on land. Sandro (shaman) is the person who leads the ritual by preparing ingredients such as areca nut, betel leaf, betel nut, gambir, tobacco, cigarettes and rice as offerings to be anchored (sea) or placed on the ground (land) in the morning while recite prayers, incantations.